If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + 4x = 5x + -11 Reorder the terms: -12 + 4x = -11 + 5x Solving -12 + 4x = -11 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -12 + 4x + -5x = -11 + 5x + -5x Combine like terms: 4x + -5x = -1x -12 + -1x = -11 + 5x + -5x Combine like terms: 5x + -5x = 0 -12 + -1x = -11 + 0 -12 + -1x = -11 Add '12' to each side of the equation. -12 + 12 + -1x = -11 + 12 Combine like terms: -12 + 12 = 0 0 + -1x = -11 + 12 -1x = -11 + 12 Combine like terms: -11 + 12 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| 12x-38=6x-4 | | 3x+36=11x-34 | | 2+4x+x=7 | | 4n^2-11n-29=-5 | | -2(x+1)+5x=3 | | -4x+10+7x=-17 | | 40=5(4x-1) | | 7(x-1)=2x+4 | | x+43=-2 | | 30-10b=2b-9 | | 5-3x=4x+11 | | --2+w=-14 | | 3+8x=87-x | | 5+5x=2x+9 | | 5+2ZIV=10 | | 6x-4=10-4x | | 98X+99L+56-65X=56+78X+9045 | | 5b-6a=11 | | 2x+2y=-22 | | 5+-6=-1 | | -40=-3x-3x-4 | | 0X=0/0 | | 456321X/0.89+987654321X=5647890643Y | | 4X(5+6)=45 | | y-(-7)=-13 | | 3x-40=2y | | 6x=x+y+10z | | 3x-8y=-62 | | 7x^2/28x^3y | | -15+10=y | | 10y=0 | | 4x+y=-16 |